Single‐Site Active Cobalt‐Based Photocatalyst with a Long Carrier Lifetime for Spontaneous Overall Water Splitting. (13th June 2017) - Liu, Wei; Cao, Linlin; Cheng, Weiren; Cao, Yuanjie; Liu, Xiaokang; Zhang, Wei; Mou, Xiaoli; Jin, Lili; Zheng, Xusheng; Che, Wei; Liu, Qinghua; Yao, Tao; et al.
Abstract: An active and stable photocatalyst to directly split water is desirable for solar‐energy conversion. However, it is difficult to accomplish overall water splitting without sacrificial electron donors. Herein, we demonstrate a strategy via constructing a single site to simultaneously promote charge separation and catalytic activity for robust overall water splitting. A single Co1 ‐P4 site confined on g‐C3 N4 nanosheets was prepared by a facile phosphidation method, and identified by electron microscopy and X‐ray absorption spectroscopy. This coordinatively unsaturated Co site can effectively suppress charge recombination and prolong carrier lifetime by about 20 times relative to pristine g‐C3 N4, and boost water molecular adsorption and activation for oxygen evolution. This single‐site photocatalyst exhibits steady and high water splitting activity with H2 evolution rate up to 410.3 μmol h −1 g −1, and quantum efficiency as high as 2.2 % at 500 nm.